Respostas

2014-01-17T15:20:31-02:00
Numerador

1/2 + 1/3 ( fazemos mmc)

(1/2)/3 + (1/3)/2

(3+2)/6= 5/6

Denominador

ab= 1/2 * 1/3= 1/6

1/1 - 1/6 (fazemos mmc)

(1/1)/6 -(1/6)/1

(6-1)/6= 5/6


Numerador + denominador

(5/6)/(5/6)= 1 
2 5 2
  • Usuário do Brainly
2014-01-17T15:29:01-02:00
A equação dada é:

  \frac{a+b}{1-ab}

Para a=1/2 e b=1/3, temos:

\frac{(a+b)}{(1-ab)}= {\frac{\frac{1}{2} +\frac{1}{3}}{1-\frac{1}{2}*\frac{1}{3}} } = \frac{ \frac{3+2}{6} }{1- \frac{1}{6} } = \frac{ \frac{5}{6} }{ \frac{6-1}{6} } = \frac{ \frac{5}{6} }{ \frac{5}{6} }=\frac{5}{6}*\frac{6}{5}=\frac{30}{30}=1


3 5 3